CASE REPORT - ACUPUNCTURE TREATMENT IN PATIENT WITH HORMONAL IMBALANCE - Arsovska, Blagica; Zhu, Jihe; Kozovska, Kristina (International Journal of Research -GRANTHAALAYAH, 2021)
Hormones play a big role and are a huge part of women’s health, including physically, mentally and emotionally. If the body produces too little or too much of some certain hormones, then the hormonal imbalance occurs. According to TCM, two organs mainly connected to the hormonal imbalances are the Kidney and the Liver. The aim of the TCM treatment for hormonal imbalance is to balance the Yin and Yang energy in the organs and the body and restore the . In this research is presented a case of a woman presented with reduced function of the thyroid gland and hormonal imbalance. Before starting the treatment the results are showing increased levels of TSH (8.08 /ml), LH (12.30 /ml) and FSH (15.70 /ml) and decreased levels of fT4 (9.78 /L). After the treatment the TSH (2.79 /ml), fT4 (14.00 /L) and LH (7.93 /ml) were normalized and FSH (12.20 /ml) was decreased with only 7 treatments within 7 weeks. Acupuncture points used in the treatment are: DU4 (MingMen), DU14 (DaZhui), DU20 (BaiHui), RN6 (QiHai), RN4 (QuanYuan), BL15 (XinShu), BL20 (PiShu), GB20 (FengChi), ST9 (RenYing), LI4 (HeGu), BL23 (ShenShu), LR2 (TaiChong), SP6 (SanYinJiao), ST36 (ZuSanLi), SP9 (YinLingQuan), KI3 (TaiXi) and points located on the neck (front and back). Acupuncture as part of the TCM can effectively help the patients struggling with hormonal imbalances to balance and regulate the hormones and harmonize the metabolism, nervous, reproductive and endocrine system.